Whole genome and whole transcriptome genomic profiling of a metastatic eccrine porocarcinoma - Thibodeau, My Linh (NPJ Precis Oncol, 2018)
Eccrine porocarcinomas (EPs) are rare malignant tumours of the intraepidermic sweat gland duct and most often arise from benign eccrine poromas. Some recurrent somatic genomic events have been identified in these malignancies, but very little is known about the complexity of their molecular pathophysiology. We describe the whole genome and whole transcriptome genomic profiling of a metastatic EP in a 66-year-old male patient with a previous history of localized porocarcinoma of the scalp. Whole genome and whole transcriptome genomic profiling was performed on the metastatic EP. Whole genome sequencing was performed on blood-derived DNA in order to allow a comparison between germline and somatic events. We found somatic copy losses of several tumour suppressor genes including APC, PTEN and CDKN2A, CDKN2B and CDKN1A. We identified a somatic hemizygous CDKN2A pathogenic splice site variant. De novo transcriptome assembly revealed abnormal splicing of CDKN2A p14(ARF) and p16(INK4a). Elevated expression of oncogenes EGFR and NOTCH1 was noted and no somatic mutations were found in these genes. Wnt pathway somatic alterations were also observed. In conclusion, our results suggest that the molecular pathophysiology of malignant EP features high complexity and subtle interactions of multiple key genes. Cell cycle dysregulation and CDKN2A loss of function was found to be a new potential driver in EP tumourigenesis. Moreover, the combination of somatic copy number variants and abnormal gene expression perhaps partly related to epigenetic mechanisms, all likely contribute to the development of this rare malignancy in our patient.